Properties of singular integrals in terms of maximal functions measuring smoothness - Rzaev, Rahim M. (Eurasian Mathematical Journal, 2013)
This paper is devoted to the study of certain maximal functions measuring smoothness, related function spaces, and properties of multidimensional singular integrals. In this work we essentially use the relation between maximal functions measuring smoothness and local oscillation of functions.